2020
DOI: 10.1016/j.actatropica.2019.105188
|View full text |Cite
|
Sign up to set email alerts
|

Molecular eco-epidemiology on the sympatric Chagas disease vectors Triatoma brasiliensis and Triatoma petrocchiae: Ecotopes, genetic variation, natural infection prevalence by trypanosomatids and parasite genotyping

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
1
16
0
6
Order By: Relevance
“…It was also shown that this high prevalence of natural infection is combined with high populational densities of T. brasiliensis in this state if compared to Paraíba [8]. These findings were confirmed by several authors throughout multiples approaches [23,43,44,45,46,47]. Noteworthy, even the populations that fed on cavies were not highly infected in Paraíba state.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It was also shown that this high prevalence of natural infection is combined with high populational densities of T. brasiliensis in this state if compared to Paraíba [8]. These findings were confirmed by several authors throughout multiples approaches [23,43,44,45,46,47]. Noteworthy, even the populations that fed on cavies were not highly infected in Paraíba state.…”
Section: Discussionsupporting
confidence: 68%
“…Five sylvatic populations were found to feed on reptiles and one peridomestic. Recently, it was found that reptiles are the main food source (86%) for T. petrocchiae [45]-a triatomine that cohabits with T. brasiliensis [23]. Indeed, sporadic blood meals on coldblooded animals (such as frogs) have already been observed for T. brasiliensis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These last authors also reported di culty of differentiating T. cruzi from other morphologically similar protozoa (Blastocrithidia triatomae e T. rangeli). It is important to note that T. rangeli has already been found in T. brasiliensis in the Rio Grande do Norte (Lima-Oliveira et al, 2019). However, given the lack of statistical evidence, we suggest the OM is still valid to estimate T. cruzi prevalence if insects are fresh and alive.…”
Section: Discussionmentioning
confidence: 79%
“…Triatoma lenti was notified in two Brazilian states, namely, Bahia and Goia ´s [31,51,53]. Triatoma sherlocki is an endemic species from Bahia [50,54]. Finally, the subspecies T. b. macromelasoma, described based on melanic forms of T. b. brasiliensis found at home in the state of Pernambuco [31,51], was redescribed and revalidated by Costa et al [42].…”
Section: Introductionmentioning
confidence: 99%